Association of the TG/HDL-C and Monocyte Count/HDL-C Ratios with Coronary Artery Disease in Non-ST Segment Elevation Myocardial Infarction - Uğur Küçük; Recep Kurt (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2019)
Monocyte Count/HDL ratio (MHR) is a simple and inexpensive parameter used as a risk predictor in patients diagnosed with myocardial infarction (MI). This study aims to investigate the association between Triglyceride/HDL-C (TG/HDL-C) ratio and coronary artery disease in patients diagnosed with non-ST segment elevation MI (NSTEMI). Total of 100 patients, 50 patients with NSTEMI and 50 healthy individuals, who had admitted to the cardiology outpatient clinic between January 2018 and January 2019 included in the study. Higher monocyte count, MHR, and TG/HDL-C ratios detected in patients with coronary artery disease in comparison to healthy individuals. Although monocyte count was higher in NSTEMI group, the difference was not statistically significant (p=0.101). There was an increase in the MHR NSTEMI group when compared against the control group (p